2004
DOI: 10.1002/elan.200402778
|View full text |Cite
|
Sign up to set email alerts
|

Flow Injection Amperometric Detection at Enzyme‐Modified Gold Nanoelectrodes

Abstract: Gold nanotubular electrode ensembles were prepared by using electroless deposition of the metal within the pores of polycarbonate particle track-etched membranes. Glucose oxidase (Gox), used as a model enzyme, has been immobilized onto preformed self-assembled monolayers (mercaptoethylamine or mercaptopropionic acid) on electroless gold via cross-linking with glutaraldehyde or covalent attachment by carbodiimide coupling. Flowinjection analysis systems in flow-through or wall-jet configurations using these Gox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
1
40
1
1
Order By: Relevance
“…For many electroanalytical applications the surface of electrodes in general, and NEEs in particular [19,20] can be modified either with catalysts, mediators or molecular recognition elements. Therefore the electrochemical behavior of surface-confined redox species was also examined here on the etched NEEs.…”
Section: Electrochemistry Of Adsorbed Species At 3d-neesmentioning
confidence: 99%
“…For many electroanalytical applications the surface of electrodes in general, and NEEs in particular [19,20] can be modified either with catalysts, mediators or molecular recognition elements. Therefore the electrochemical behavior of surface-confined redox species was also examined here on the etched NEEs.…”
Section: Electrochemistry Of Adsorbed Species At 3d-neesmentioning
confidence: 99%
“…NEEs are useful electrochemical tools for biosensors development [40,41], for the measurement of (high) charge transfer rate constants [35] and for solving adsorption related problems [36]. With respect to the latter issue, it was shown that operating in very diluted solutions of the analytes (thanks to the very low detection limits achievable at NEEs) it was possible to obtain diffusion-controlled responses even for molecules such as some phenothiazines [35] or redox proteins such as cytochrome c [36], which can adsorb on electrode surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 However, a key limitation in this approach is the requirement for molecular oxygen as an oxidising agent. Further to this, relatively high overpotentials are required to reduce oxygen or oxidize the enzymatic product H 2 O 2 , is also sufficient to reduce or oxidize common interferents normally present in biological fluids.…”
Section: Resultsmentioning
confidence: 99%